Plasmonic anapole metamaterial for refractive index sensing - Yao, Jin (2023)
Electromagnetic anapole mode is a nonradiative state of light originating from the deconstructive interference of radiation of the oscillating electric and toroidal dipole moments. The high quality anapole-related resonances can be used in enhancing nonlinear electromagnetic properties of materials and in sensor applications. In this work, we experimentally demonstrate plasmonic anapole metamaterial sensor of environmental refractive index in the optical part of the spectrum. Our results show that the sensor exhibits high sensitivity to the ambient refractive index at the level of 330 nm/RIU and noise floor of 8.7 × 10-5 RIU. This work will pave the way for applications of anapole metamaterials in biosensing and spectroscopy.